Analysis Development Planning: Case Study Lubuk Cemara Area, Serdang Bedagai Regency Sumatra - Rambe, Dhea Nita Syafina; Lubis, Irsad (Reviu Akuntansi, Manajemen, dan Bisnis, 2025)
Purpose: This research aims to understand the development planning in Lubuk Cemara Village, Perbaungan District, and the factors influencing the development planning in Lubuk Cemara Village, Perbaungan District. Methodology/approach: This type of research is descriptive qualitative research. The number of informants is 8 informants. The data collection methods used in this research are questionnaires, interviews, and documentation. The types of data used are qualitative data and quantitative data. Results/findings: The research results indicate that the development planning process in Lubuk Cemara Village, Perbaungan District, has not yet shown optimal improvement in community welfare. This can be seen from the suboptimal ability of village government officials in conducting good and targeted development planning and in overseeing the development planning process. Conclussion: Based on the research conducted on the development planning in Lubuk Cemara Village, Perbaungan District, the author can conclude that the analysis of the development planning in Lubuk Cemara Village, Perbaungan District, has not yet shown an optimal improvement in social welfare. This can be seen from the suboptimal ability of village government officials in conducting effective and targeted development planning and in overseeing development planning. Limitations: The factors that influence the planning of the development of LubukCemara Village are: the amount of cost, facilities and infrastructure, and the implementation time. Contribution: The data analysis technique used is based on a theory that consists of data collection, data reduction, data presentation, and conclusion drawing.